Pengaruh Pendidikan, Pemahaman Akuntansi, dan Pengalaman Kerja terhadap Penyusunan Laporan Keuangan - Nurwanto Nurwanto; Riana Rachmawati Dewi; Endang Masitoh (Owner : Riset dan Jurnal Akuntansi, 2022)
The preparation of financial statements can be influenced by education, understanding of accounting, and work experience. This study aims to determine the effect of education, accounting understanding, and work experience on the preparation of financial statements. This research is quantitative. The number of samples was 60 employees of the Surakarta Islamic Study Council Foundation which were selected using saturated sampling. Multiple linear regression analysis was used as a data analysis technique. This research is shown based on the acquisition of t count 2,263 > t table 2,003, sig. of 0.028 <0.05, meaning that it accepts H1, meaning that education has a significant positive effect on the preparation of the financial statements of the Surakarta Islamic Study Council Foundation. Obtaining t arithmetic 4.087 > t table 2.003, sig. of 0.000 <0.05, meaning that it accepts H2, meaning that accounting understanding has a significant positive effect on the preparation of the financial statements of the Surakarta Islamic Study Council Foundation. The value of t arithmetic is 4.768 > t table 2.003, sig. 0.000 <0.05, means accepting H3, meaning that work experience has a positive influence on the preparation of the financial statements of the Surakarta Islamic Study Council Foundation. The conclusion is that education, understanding of accounting, and work experience have a significant positive effect on the preparation of financial statements at the Surakarta Islamic Study Council Foundation.